Investigating false memories among "winners" and "losers" in the prisoner's dilemma. Issue 10 (26th November 2022) - Greene, Ciara M.; Donnelly, Oisín; Garvin, Chris; Murphy, Gillian
ABSTRACT: Many legal cases hinge on evaluating the veracity of two versions of events ("he said, she said"). Expert witnesses are often called upon to testify on the malleability of memory, most often testifying for the defence. This may lead to the theoretically unfounded assumption that it is only victims who are vulnerable to distorted memories of a crime. Inspired by this question, we conducted a series of five experiments in which 2010 participants played a novel version of the Prisoner's Dilemma. Participants could either betray their partner in the game ("winners") or be betrayed by their partner ("losers"). We exposed participants to misinformation concerning the other player's statements to assess whether winners and losers may be differentially susceptible to false memories of the event in question. Across our experiments, including where real financial rewards were at stake, we found that winners were just as susceptible as losers to memory distortion. We highlight the need to consider the possibility of faulty memory affecting all parties to in legal cases, though further research is needed beyond this highly artificial paradigm.